The Hermeneutics of Love in Mizrahi Diaspora - Firestone, Asher (WritingThreeSixty, 2025)
This paper investigates the discursive shifts necessary to establishing an anti-Zionist Jewish diaspora formed in part by Mizrahi reality. Using what Chela Sandoval calls the “praxis stage of the hermeneutics of love,” I consider what formal tasks Jewish communities are responsible for in a decolonizing Palestine. This work entails the contextualization of race within Israel’s formation of Jewish identity and the ongoing metabolization of Arabness to do so. Ultimately, I pose an advanced question for diaspora studies: How can a nation-state be rejected and subsequently disbanded without its most subjugated populations increasingly harmed in the “liberatory” process?